Breaking the sheep's back : the shocking true story of the decline and fall of the Australian wool industry - Massy, Charles, (University of Queensland Press, 2011)
From the author of the influential The Australian Merino comes the shocking true story of the decline and fall of the Australian wool empire a tale that features a brace of Australian characters, political skulduggery and betrayal on a massive scale. Breaking the Sheep's Back is the untold story of Australia's biggest business disaster.